SARM1 activation induces reversible mitochondrial dysfunction and can be prevented in human neurons by antisense oligonucleotides - Andrea Loreto; Kaitlyn M.L. Cramb; Lucy A. McDermott; Christina Antoniou; Ilenia Cirilli; Maria Claudia Caiazza; Elisa Merlini; Peter Arthur-Farraj; W. Daniel du Preez; Elliot D. Mock; Hien T. Zhao; David L. Bennett; et al. (Neurobiology of Disease, 2025)
SARM1 is a key regulator of a conserved program of axon degeneration increasingly linked to human neurodegenerative diseases. Pathological SARM1 activation causes rapid NAD consumption, disrupting cellular homeostasis and leading to axon degeneration. In this study, we develop antisense oligonucleotides (ASOs) targeting human SARM1, demonstrating robust neuroprotection against morphological, metabolic, and mitochondrial impairment in human iPSC-derived dopamine neurons induced by the lethal neurotoxin vacor, a potent SARM1 activator. Furthermore, our findings reveal that axon fragmentation can be prevented, and mitochondrial dysfunction reversed using the NAD precursor nicotinamide, a form of vitamin B3, even after SARM1 activation has occurred, when neurons are already unhealthy. This research identifies ASOs as a promising therapeutic strategy to block SARM1, and provides an extensive characterisation and further mechanistic insights that demonstrate the reversibility of SARM1 toxicity in human neurons. It also identifies the SARM1 activator vacor as a specific and reversible neuroablative agent in human neurons.